St. Philips footbridge in Bristol: A holistic design as a driver for urban regeneration. Issue 2 (15th January 2019) - Beade‐Pereda, Héctor; McElhinney, John; Barbulescu, Bogdan
Abstract: The transformation of an area originally used for railway maintenance into a new neighbourhood in the city centre is one of the most important urban development projects being carried out in Bristol. The new St Philips footbridge spans the River Avon contributing to provide the needed accessibility for development to a site previously isolated by several infrastructures and the watercourse. The footbridge is an innovative solution to a complex crossing problem: the connection of two banks with a significant elevation and appearance difference and one of them being developed to high architectural standards faster than the other. The design should be appropriate for both immediate and medium‐term scenarios and to harmoniously coexist with the close existing bridges and the future buildings. The bridge is a 50m‐span and 4‐m wide steel beam with a forked geometry, hosting a ramp for disabled and cyclists and a staircase as part of its own structure to maximise functionality. The design approach to generate its shape was at the same time structural, aesthetical, and functional. Thanks to this holistic approach, the bridge is compact, simple, elegant and clearly legible for both footbridge and river path users.